Noncommunicable Disease (NCD) strategic plans in low- and lower-middle income Sub-Saharan Africa: framing and policy response - Chantelle Boudreaux; Christopher Noble; Matthew M. Coates; Jason Kelley; Martin Abanda; Alexander Kintu; Amy McLaughlin; Andrew Marx; Gene Bukhman (Taylor & Francis Group, 2020)
Background Global efforts to address NCDs focus primarily on 4-by-4 interventions - interventions to prevent and treat four groups of conditions affecting mainly older adults (some cardiovascular disease and cancers, type 2 diabetes, chronic respiratory disease) and four associated risk factors (alcohol, tobacco, poor diets, and physical inactivity). However, the NCD burden in Sub-Saharan Africa (SSA) is composed of a more diverse set of conditions, driven by a more complex group of risks, and impacting all segments of the population. Objective To document the NCD priorities identified by NCD strategic plans, to characterize the proposed policy response, and to assess the alignment between the two. Methods Using a two-part conceptual framework, we undertook a descriptive study to characterize the framing and overall policy response of strategic plans from 24 low- and lower-middle-income countries across SSA. Results The national situation assessments that ground strategic plans emphasize a diversity of conditions that range in terms of severity and frequency. These assessments also highlight a wide diversity of factors that shape this burden. Most include discussions of a broad range of behavioral, structural, genetic, and infectious risk factors. Plans endorse a more narrow response to this diverse burden, with a focus on primary and secondary prevention that is generally convergent with the objectives established in global policy documents. Conclusions Broadly, we observe that plans developed by countries in SSA recognize the heterogeneity of the NCD burden in this region. However, they emphasize interventions that are consistent with global strategies focused on preventing a narrower set of cardiometabolic risk factors and their associated diseases. In comparison, relatively few countries detail plans to prevent, treat, and palliate the full scope of the needs they identify. There is a need for increased support for bottom-up planning efforts to address local priorities.